Synthesis, Structural Characterization, and Dehydration Analysis of Uranyl Zinc Mellitate, (UO2)Zn(H2O)4(H2mel)·2H2O. Issue 12 (8th February 2013) - Olchowka, Jakub; Volkringer, Christophe; Henry, Natacha; Loiseau, Thierry
Abstract: A new heterometallic uranyl zinc carboxylate, (UO2 )Zn(H2 O)4 (H2 mel)· 2H2 O, has been hydrothermally prepared (150 °C, 24 h) by using 1, 2, 3, 4, 5, 6‐benzenehexacarboxylic acid (mellitic acid) as organic linker in order to form a three‐dimensional network. Four of the six carboxylate groups of the mellitate ligand interact with mononuclear uranyl or zinc cations, which are eightfold (hexagonal bipyramid, UO8 ) or sixfold [octahedron, ZnO2 (H2 O)4 ] coordinated, respectively. The remaining free carboxylate arms of the mellitate species preferentially interact through hydrogen bonds with water molecules trapped within the framework. Thermogravimetric and X‐ray thermodiffraction (up to 800 °C) analyses and in situ infrared spectroscopy (up to 210 °C) indicated that both free and bound water species are evacuated from the structure in one step between 80 and 170 °C, followed by its transformation into an unknown, anhydrous, poorly crystalline phase [UO2 Zn(mel)] up to 320 °C. After the formation of an amorphous phase, the re‐crystallization of oxides α‐ZnU3 O10 and ZnO was observed from 460 °C. The fluorescence spectrum of the as‐synthesized uranyl zinc mellitate shows the six bands that are typical for vibronic couplings of the [O=U=O] 2+ moiety. Abstract : A mixed zinc–uranyl compound was hydrothermally synthesized by using mellitic acid, an aromatic hexacarboxylic acid. Its crystal structure is a 3D coordination polymer of uranyl‐centered and zinc‐centered mononuclear units linked to each other via mellitate ligands. The dehydration process was investigated by in situ infrared spectroscopy.